Introduction to Southern Highbush Blueberry Cultivation in Containers - Gerardo H. Nunez; Martin Zapien; Douglas Phillips (EDIS)
Blueberry bushes prefer well drained, acidic soils with high organic matter content. These soil characteristics are not common in many parts of the world. Thus, blueberries are traditionally grown in soils amended with pine bark and elemental sulfur. The need to create optimum conditions for the roots of blueberry bushes has recently led to blueberry cultivation in containers filled with soilless substrates. The intended audience for this publication is commercial blueberry growers. The purpose of this publication is to complement existing information sources by introducing the materials and practices used for blueberry cultivation on container-based farms.